Microscopic mechanism of the L12–D019 phase transformation in a Co-base single crystal superalloy - Karpstein, Nicolas; Laplanche, Guillaume; Saksena, Aparna; Zehl, Rico; Bezold, Andreas; Horst, Oliver M.; Bürger, David; Kostka, Aleksander; Zenk, Christopher; Neumeier, Steffen; Gault, Baptiste; Ludwig, Alfred; et al. (Acta Materialia, 2025)
In γ′-strengthened superalloys based on the Co-Al-W system, the stability of the γ′ phase is often limited, as it is found to transform into other phases such as B2 and D019 after long-term annealing. To explore the details behind the annealing-induced transformation from the metastable L12-γ′ phase to the thermodynamically stable D019-χ phase in the single-crystalline Co-base superalloy ERBOCo-VF60 (Co79.8Al8.9W9.0Ta2.3 in at.%), scanning transmission electron microscopy and atom probe tomography are employed. Due to the structural similarity between the L12 and D019 structures, coherent plate-shaped χ precipitates are formed in the γ/γ′ microstructure parallel to 111 planes through a shear-based transformation mechanism. While the χ phase precipitates slowly during isothermal aging, its formation can be significantly accelerated locally by coating the superalloy with a Cr-rich layer, which indirectly stabilizes the χ phase as revealed by thermodynamic calculations. This procedure allowed us to obtain an intermediate (incomplete) state of χ-phase formation in terms of both crystal structure and composition. By characterizing the partial dislocations at the tip of growing χ precipitates, the microscopic details of the shear-based cubic-to-hexagonal transformation from L12 to D019 are uncovered. The compositional aspect of the transformation involves a significant diffusion-mediated enrichment of W in the χ phase, accompanied by a simultaneous W depletion in the γ′ phase, leading to its transformation to the γ phase.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Atom probe tomography; Cobalt-base superalloys; Phase transformations; Stacking faults; Transmission electron microscopy